2022
DOI: 10.3390/su14148480
|View full text |Cite
|
Sign up to set email alerts
|

How Has the COVID-19 Pandemic Influenced the Tourism Behaviour of International Students in Poland?

Abstract: Nearly 20 years after the SARS (Severe Acute Respiratory Syndrome) epidemic, we are facing another COVID-19 pandemic. Therefore, the aim of our study was to analyse the impact of the COVID-19 pandemic on the tourism behaviour of international students in Poland. We paid attention to the overall impact of the pandemic on life, travel, choice of tourist destination, tourism activity, ecotourism preference, and health and safety issues. We formulated two research questions: What areas of international student tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Another example of research was conducted by Szlachcik et al [68] who investigated the impact of the pandemic on life, travel, choice of tourist destination, tourist activity, eco-tourism preferences and health and safety issues identified by international students from Europe and Asia studying at universities in Warsaw (a group of 719 respondents). The research showed that the COVID-19 pandemic had a significant impact on the travel behaviour of international students studying in Poland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of research was conducted by Szlachcik et al [68] who investigated the impact of the pandemic on life, travel, choice of tourist destination, tourist activity, eco-tourism preferences and health and safety issues identified by international students from Europe and Asia studying at universities in Warsaw (a group of 719 respondents). The research showed that the COVID-19 pandemic had a significant impact on the travel behaviour of international students studying in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Szlachciuk and co-authors among 719 foreign students studying in Poland showed that the COVID-19 pandemic had a significant impact on their travel behaviour and, in terms of changing their motives for choosing travel destinations, the choice of destination and standard of accommodation, hygiene conditions and their sense of security [68].…”
Section: Discussionmentioning
confidence: 99%
“…The second part of the questionnaire (10 items) concerned the consumers’ purchasing behavior during the COVID-19 pandemic. The results of the analysis of 20 items concerning tourism choices were published in the article “How the COVID-19 pandemic influences the tourism behavior of the international students in Poland?” [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above conditions, the purpose of our research is to analyze the shopping behavior of international students (Asian vs European) studying in Poland. This is the second part of our research; the first was on the tourism behavior of international students [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the COVID-19 pandemic has significantly reduced the number of tourists and the output value of the tourism industry and related industrial chains. Moreover, it also significantly decreased the ability to absorb employment and severely impacted the development of the tertiary industry and the job market in many countries, especially those that rely on tourism income (34)(35)(36). Of course, COVID-19 has also accelerated the adjustment of the tourism industry and the market competition pattern, such as digital tourism, innovation in tourism products, and the improvement of tourism services.…”
Section: Introductionmentioning
confidence: 99%